Hygrocybe umbilicata sp. nov., with first generic report for Bangladesh and its phylogenetic placement - Hosen, Md. Iqbal; Li, Tai-Hui; Aminuzzaman, F. M.; Islam, Md. Rafiqul (Phytotaxa, 2016)
Hygrocybe umbilicata, a new waxcap of Hygrophoraceae, is formally described from Bangladesh based on morphological data and molecular evidence of the nuclear ribosomal internal transcribed spacer (ITS) region. This species represents the first record of the genus Hygrocybe for this country. It can be easily recognized by its brilliantly scarlet red with umbilicate pileus, lemon yellow stipe, white short decurrent and distant lamellae, subglobose basidiospores, and abundant clamp connections in tissues. This species belongs to genus Hygrocybe subg. Pseudohygrocybe sect. Coccineae subsect. Squamulosae. Detailed description, color photographs and illustrations of the new species are presented.